Overview of Cell Death Mechanisms Induced by Rose Bengal Acetate-Photodynamic Therapy - Elisa Panzarini; Valentina Inguscio; Luciana Dini (International Journal of Photoenergy)
Photodynamic Therapy (PDT) is a non-invasive treatment for different pathologies, cancer included, using three key components: non-toxic light-activated drug (Photosensitizer, PS), visible light, and oxygen. Their interaction triggers photochemical reactions leading to Reactive Oxygen Species (ROS) generation, that mediate cytotoxicity and cell death. In the present paper, the most important findings about the synthetic dye Rose Bengal Acetate (RBAc), an emerging photosensitizer for its efficient induction of cell death, will be reported with the aim to integrate RBAc phototoxicity to novel therapeutic PDT strategies against tumour cells. After its perinuclear intracellular localization, RBAc causes multiple subcellular organelles damage, that is, mitochondria, Endoplasmic Reticulum (ER), lysosomes, and Golgi complex. Indeed, RBAc exerts long-term phototoxicity through activation of both caspase-independent and- dependent apoptotic pathways and autophagic cell death. In particular, this latter cell death type may promote cell demise when apoptotic machinery is defective. The deep knowledge of RBAc photocytotoxicity will allow to better understand its potential photomedicine application in cancer.